2006
DOI: 10.1021/jp060164n
|View full text |Cite
|
Sign up to set email alerts
|

Architectural Control Syntheses of CdS and CdSe Nanoflowers, Branched Nanowires, and Nanotrees via a Solvothermal Approach in a Mixed Solution and Their Photocatalytic Property

Abstract: Wurtzite CdS and CdSe nanostructures with complex morphologies such as urchin-like CdS nanoflowers, branched nanowires, and fractal nanotrees can be produced via a facile solvothermal approach in a mixed solution made of diethylenetriamine (DETA) and deionized water (DIW). The morphologies of CdS and CdSe nanocrystals can be easily controlled via tuning the volume ratio of DETA and DIW. Urchin-like CdS nanoflowers made of CdS nanorods are in a form of highly ordered hierarchical structures, while the nanowires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(118 citation statements)
references
References 77 publications
4
114
0
Order By: Relevance
“…Two oppositely polar assemblies prepared under identical conditions develop entirely distinct optoelectronic properties, due to the unique spatial organization of the individual rods. Such polarity control could be a general natural phenomenon and can occur in assemblies of others materials, too, such as those reported for ferroelectric, ferromagnetic, piezoelectric materials, etc., having an element of asymmetry (30,31).…”
Section: Resultsmentioning
confidence: 99%
“…Two oppositely polar assemblies prepared under identical conditions develop entirely distinct optoelectronic properties, due to the unique spatial organization of the individual rods. Such polarity control could be a general natural phenomenon and can occur in assemblies of others materials, too, such as those reported for ferroelectric, ferromagnetic, piezoelectric materials, etc., having an element of asymmetry (30,31).…”
Section: Resultsmentioning
confidence: 99%
“…NiO hollow microspheres showed greater catalytic activity than rods 6 A special class of 2D NSs self-assembled into a 3D architecture is another important research area in photocatalysis. [6][7][8][9][10][11] Layered titanates have been introduced for H 2 production as a result of their proton-exchange capability in the absence of co-catalysts. 223 …”
Section: Two-dimensional Nanostructuresmentioning
confidence: 99%
“…[18][19][20]. A number of reports have described the growth of CdS branched nanostructures in colloidal systems [21][22][23][24][25][26]. In contrast, only a few studies on CdS straight nanorod arrays on substrates have been reported [27][28][29][30][31] [32], where CdS branched nanorod arrays were fabricated via a one-step hydrothermal approach employing cadmium sulfide and thiourea as starting agents.…”
Section: Introductionmentioning
confidence: 99%